1998
DOI: 10.1021/jo972198k
|View full text |Cite
|
Sign up to set email alerts
|

Benzylchlorocarbene:  Origins of Arrhenius Curvature in the Kinetics of the 1,2-H Shift Rearrangement

Abstract: Benzylchlorocarbene (1, BCC) was generated photochemically from benzylchlorodiazirine (2) in isooctane, methylcyclohexane (MCH), and tetrachloroethane (TCE) at temperatures from ∼30 to −75 °C. At −70 °C in isooctane, the identified products included Z/E-β-chlorostyrenes 4 (46.6%), α-chlorostyrene 5 (2.4%), 1,1-dichloro-2-phenylethane 6 (1.9%), a BCC-isooctane insertion product 8 (5.5%), carbene dimers 9 (3.8%), and azine 3 (30%). The significant incursion of intermolecular products 3, 8, and 9 implies that las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 25 publications
5
18
0
Order By: Relevance
“…Thus, not all of the carbene can be diverted to cyclopropane, even at infinite concentration of TME (Scheme ). Furthermore, some dependence of the intercept of plots of [ 3 /adduct (e.g., 4 )] versus 1/[alkene] on the nature of the alkene was found, as predicted by the carbene−alkene complex mechanism . Subsequently, it was found that the E / Z ratio of β-chlorostyrenes varies with [TME], which is also consistent with Scheme .…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Thus, not all of the carbene can be diverted to cyclopropane, even at infinite concentration of TME (Scheme ). Furthermore, some dependence of the intercept of plots of [ 3 /adduct (e.g., 4 )] versus 1/[alkene] on the nature of the alkene was found, as predicted by the carbene−alkene complex mechanism . Subsequently, it was found that the E / Z ratio of β-chlorostyrenes varies with [TME], which is also consistent with Scheme .…”
Section: Introductionsupporting
confidence: 82%
“…Subsequently, it was found that the E / Z ratio of β-chlorostyrenes varies with [TME], which is also consistent with Scheme . The kinetics and spectroscopy of benzylchlorocarbene have also been studied by laser flash photolysis techniques. ,
1
2
…”
Section: Introductionmentioning
confidence: 99%
“…For the second criterion, the ratio A H /A D was 0.28 (A H = 97.9, A D = 344.2), much less than 0.7, which implies tunneling. This suggestion is supported by ample precedent for tunneling in 1,2-H shifts, particularly in carbenes (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), and also in cyclopentadienes (14). The barriers in these reactions vary from ca.…”
Section: Methodsmentioning
confidence: 66%
“…Azine can be formed by several mechanisms including the reaction of a carbene with its diazirine precursor. This reaction is very fast and complicates analysis of the kinetics of benzylchlorocarbene …”
Section: Resultsmentioning
confidence: 99%